Engineers’ abilities influence spatial perspective changing - Paola Verde; Gregorio Angelino; Francesco Piccolo; Paolo Corrazzo; Laura Piccardi; Raffaella Nori (Universitas Diponegoro, 2019)
In this paper we studied the effect of engineering expertise in providing directional judgments. We asked two groups of people, engineers and non-engineers, to observe and memorize five maps, each including a four-point path, for 30 sec. The path was then removed and the participants had to provide two directional judgments: aligned (the imagined perspective on the task was the same as the one just learned), and counter-aligned (the imagined perspective on the task was rotated by 180°). Our results showed that engineers are equally able to perform aligned and counter-aligned directional judgments. The alignment effect due to the distance from the learning perspective was, in fact, shown only by non-engineers. Results are discussed considering engineering both learning expertise and specific predisposition.